Definition of REST web services with JSON schema. (16th December 2016) - Barbaglia, Guido; Murzilli, Simone; Cudini, Stefano
Summary: The Web has evolved from being a collection of documents to a collection of interconnected services that interoperate throughout the Internet. Web services are a natural consequence of this evolution. The web services model was initially centered around the eXtensible Markup Language (XML). Such services can be described by Web Services Description Language documents that are formally defined through the XML Schema Definition language. However, in recent years the popularity of XML‐based web services has declined, as more developers favor JavaScript Object Notation (JSON)‐based alternatives. Although the use of the latter language is spreading, no official standard to formally describe JSON documents exists. The aim of this article is to demonstrate how JSON Schema, and particularly the JSON Hyper Schema extension, is suitable to describe JSON‐based web services that follow the REST architectural pattern. Copyright © 2016 John Wiley & Sons, Ltd.